Religious burning as a potential major source of atmospheric fine aerosols in summertime Lhasa on the Tibetan Plateau. (May 2018) - Cui, Yu Yan; Liu, Shang; Bai, Zhixuan; Bian, Jianchun; Li, Dan; Fan, Kaiyu; McKeen, Stuart A.; Watts, Laurel A.; Ciciora, Steven J.; Gao, Ru-Shan
Abstract: We carried out field measurements of aerosols in Lhasa, a major city in the Tibetan Plateau that has been experiencing fast urbanization and industrialization. Aerosol number size distribution was continuously measured using an optical particle size spectrometer near the center of Lhasa city during the Asian summer monsoon season in 2016. The mass concentration of fine particles was modulated by boundary layer dynamics, with an average of 11 μg m −3 and the high values exceeding 50 μg m −3 during religious holidays. Daytime high concentration coincided with the religious burning of biomass and incense in the temples during morning hours, which produced heavy smoke. Factor analysis revealed a factor that likely represented religious burning. The factor contributed 34% of the campaign-average fine particle mass and the contribution reached up to 80% during religious holidays. The mass size distribution of aerosols produced from religious burnings peaked at ∼500 nm, indicating that these particles could efficiently decrease visibility and promote health risk. Because of its significance, our results suggest that further studies of religious burning, a currently under-studied source, are needed in the Tibetan Plateau and in other regions of the world where religious burnings are frequently practiced. Graphical abstract: Image 1 Highlights: The PBL dynamics played a key role in modulating aerosol pollution in Lhasa. The PM was substantially higher during religious holidays compared to non-holidays. Religious burnings may significantly contribute to aerosol mass in summertime Lhasa.